1995
DOI: 10.1080/00913367.1995.10673486
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Perceptions of Cigarette Brand Advertising Symbols: Awareness, Affect, and Target Market Identification

Abstract: The author assesses young children's abilities to recognize cigarette brand advertising symbols and to identify adults as the appropriate target market for cigarettes. She used nonverbal measures in interviews with children three to eight years of age to assess how recognition of cigarette brand advertising symbols is related to age, cognitive developmental level, children's affect toward cigarettes, children's evaluation of cigarettes, and children's ability to identify adults as the appropriate target market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 9 publications
(9 reference statements)
1
14
0
3
Order By: Relevance
“…The presence of an adult parent or caretaker could heighten this possibility. Henke (1994) found that 96% of her sample of 83 three-to eight-year-old children reported they disliked cigarettes. Using only an interviewer and no parent or caretaker, she found no significant effect of age for that measure.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of an adult parent or caretaker could heighten this possibility. Henke (1994) found that 96% of her sample of 83 three-to eight-year-old children reported they disliked cigarettes. Using only an interviewer and no parent or caretaker, she found no significant effect of age for that measure.…”
Section: Limitationsmentioning
confidence: 96%
“…Henke (1994) reports Joe Camel recognition at 86% for a subsample of eight-year-old children. A 1993 Roper Starch survey for the R.J. Reynolds Tobacco Company showed that 95% of a national sample of 10^ to 17-year-olds knew Joe Camel was associated with cigarettes.…”
Section: Children's Recognition Of Trade Charactersmentioning
confidence: 99%
“…Furthermore, Dubow (1995) found that adolescents generally remember advertising better than adults. In a study of younger children, Henke (1995) found that the ability to recognize the cigarette brand symbols used in advertising becomes stronger with age. This trend is also true for the ability to recognize brand advertising symbols in general.…”
Section: Agementioning
confidence: 98%
“…Some of the past studies have examined children's attitudes toward advertisements (Bakir et al 1998;Kolbe and Muehling 1995) and content analysis of children's commercials (Browne 1998;Hoek and Laurence 1993;Hoek and Sheppard 1990;Macklin and Kolbe 1984). Other studies examined effectiveness of audio and visual versions of ad breaks in an advergame context with children (An and Stern 2011), effects of television commercial violence on children (Brocato et al 2010), children's recall of television ad elements (Maher, Hu, and Kolbe 2006), and children's perceptions of advertising symbols (Henke 1995). In-depth analysis of children's advertisements in emerging markets is still needed, as well as cross-cultural studies on children's advertising, which are to date not only very limited (Browne 1998) but also focused only on industrialized markets.…”
mentioning
confidence: 96%